Floristic-structural heterogeneity of the tree component in a system of forest fragments in the southernplateau of Santa Catarina, Brazil Heterogeneidade florístico-estrutural do componente arbóreo em um sistema de fragmentos florestais no planalto sul catarinense - Negrini M. (2014)
© 2014, Sociedade de Investigacoes Florestais. All rights reserved.The goal of this study was to evaluate the spatial, floristic and structural variations of the tree component of a fragments system of Araucaria Forest in the uplands of the state of Santa Catarina, Brazil. For this sake, within four fragments, 50 parcels of 200 m2 (10 x 20 m) were allocated; their individuals with diameter at breast height (DBH), measured at 1.30 m height, > 5 cm, were identified and measured. The Importance Value Index was determined and the floristic-structural comparison among fragments was analyzed, applying a non-parametric multivariate analysis of variance (NPMANOVA). Indicator species of each fragment was determined by Indicator Species Analysis (ISA). We found 73 species, being Araucaria angustifolia (Bert.) Kuntze the most important species. There was a difference in the tree component structure of the fragments (p = 0.001); it is possible to identify indicator species for fragments 1, 2 and 3. This study showed that fragments located close to each other may present floristic-structural variations, which should be considered during strategies definition for forest management and conservation.